2017
DOI: 10.1073/pnas.1605369114
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive self-organization of Bali’s ancient rice terraces

Abstract: Spatial patterning often occurs in ecosystems as a result of a selforganizing process caused by feedback between organisms and the physical environment. Here, we show that the spatial patterns observable in centuries-old Balinese rice terraces are also created by feedback between farmers' decisions and the ecology of the paddies, which triggers a transition from local to globalscale control of water shortages and rice pests. We propose an evolutionary game, based on local farmers' decisions that predicts speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 14 publications
3
51
0
2
Order By: Relevance
“…When substance‐based concepts are used as basis for the design of solutions to problems, they risk leading to unintended outcomes because an entities’ history or relations to its environment have not been taken into account. Lansing et al () have demonstrated how standardized and decontextualized blueprint solutions such as the introduction of green revolution practices in Bali in the 1970s led to increased pest outbreaks because of a disregard of strongly contextual practices, such as collective and synchronized irrigation schedules and pest management practices which are the result of co‐evolutionary social and ecological processes. Substance‐based concepts correspond to, or ‘mirror’ immutable substances.…”
Section: Substance Ontologies: a World Of Objects Described With Nounsmentioning
confidence: 99%
“…When substance‐based concepts are used as basis for the design of solutions to problems, they risk leading to unintended outcomes because an entities’ history or relations to its environment have not been taken into account. Lansing et al () have demonstrated how standardized and decontextualized blueprint solutions such as the introduction of green revolution practices in Bali in the 1970s led to increased pest outbreaks because of a disregard of strongly contextual practices, such as collective and synchronized irrigation schedules and pest management practices which are the result of co‐evolutionary social and ecological processes. Substance‐based concepts correspond to, or ‘mirror’ immutable substances.…”
Section: Substance Ontologies: a World Of Objects Described With Nounsmentioning
confidence: 99%
“…This will enable our models to predict collective dynamics of violence outbreaks, from urban riots to popular insurrections. Thurner has used this fact in numerous previous ABMs of collective human behavior: opinion formation (Lambiotte et al 2007;Klimek et al 2008), financial investments (Thurner et al , 2013, organization of human groups (Szell et al 2010;Klimek et al 2015), emergence of cooperation , voting behavior (Klimek et al 2012), and rice farming in Bali (Lansing et al 2017).…”
Section: The Feasibility Of the Approachmentioning
confidence: 99%
“…Alternatively, synchronization could have emerged “by accident” if several farmers independently copied the cropping pattern of a neighboring farmer who had produced the highest yield the previous year. (see Lansing et al (2017) for a model of such a process) Given the autonomy over their agricultural practices (Lansing 2006; MacRae and Arthawiguna 2011), if synchronized cropping generated greater yields for farmers than they had experienced prior to synchronization, there would have been an incentive to continue synchronizing. The resulting group would have represented the earliest subak.
Fig.
…”
Section: The Emergence Of Synchronized Cropping Subaks and Associatmentioning
confidence: 99%
“…2e). In fact, Lansing et al (2017) model the emergence of synchronization among farmers and Lansing and Kremer (1993) model a similar process among subaks to illustrate this mechanism. In the latter case, each subak checks the productivity of its four nearest neighboring subaks and adopts the cropping pattern of the neighboring subak with the highest yield.…”
Section: Cultural Group Selection Mechanismsmentioning
confidence: 99%